If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f + 15 = 27 Reorder the terms: 15 + f = 27 Solving 15 + f = 27 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + f = 27 + -15 Combine like terms: 15 + -15 = 0 0 + f = 27 + -15 f = 27 + -15 Combine like terms: 27 + -15 = 12 f = 12 Simplifying f = 12
| X+9=3x+4 | | (25*2)+(15*y)=30500 | | 10p+3-4p=4p-10 | | 12-4=3 | | .04x+3(3000-x)= | | (25*0)+(15*y)=30500 | | T=x-6 | | 6z+0.36=24072 | | t+0.9=9 | | 2(x-1)+3(3x+4)=4 | | e^14x=110 | | h=-16t^2+24t | | 0.007x^2+0.02x-150=0 | | 2x^2+8x-15= | | 9z+5=11z-5 | | 10-4r=-2(3r+5)+7r | | 2x-x+6x+5=41 | | 5(-4)=-3x+44 | | -6(10+p)=-150 | | 20x-x^2-150=0 | | 10+6x-4=26+2x | | -7w+4=10 | | 8x+24+2x+96=180 | | -2n+4n-7=0 | | -12+x=-3 | | 3y-6=6(y-2) | | -5-4x-2x=-7 | | 12+3x-3=15-4x | | (12x^2)+x+4=0 | | 3(5x-7)=5(3x+4) | | 3x+6x-6=18 | | 4x+4+2x+38=180 |